Hubungan Konsumsi Junk Food, Status Gizi dan Aktivitas Fisik terhadap Menarche pada Remaja di MTSN 2 Kabupaten Tangerang Tahun 2022 - Mayang Fajar Dwiwana; Retno Puji Astuti (SCIPRO Foundation, 2023)
Introduction: Menarche is the first menstruation which is the hallmark of a healthy woman's maturity. Indonesia experienced a decline in menarche based on the results of Riskesdas in 2013 there were 5.2% of children in Indonesia entering the age of menarche under the age of 12 years. Modernization and instantiation of lifestyle are believed to play a role in the shift in the age of menarche, such as consumption of junk food, nutritional status, and physical activity. Objectives: This study aimed to determine the relationship between junk food consumption, nutritional status, and physical activity on menarche in adolescents at MTS N 02 Tangerang Regency. Method: This study uses a cross-sectional research design with quantitative research. The population of this research is students in grades 7, 8, and 9 of MTS N 02 Tangerang Regency with a total of 461 students. The sample of this research is 90 respondents taken by simple random sampling method. The measuring instrument for data collection in this study used a questionnaire sheet. This study uses chi-square test data analysis. Result: The results showed that most respondents menarche at 11-12 years old. The results of data analysis showed that there was no significant relationship between junk food consumption (p=0.261) (>0.05), nutritional status (p=0.560) (>0.05), and physical activity (p=0.901) (>0, 05) with menarche in adolescents in MTS N 02 Tangerang Regency. Conclusion: This study's conclusion shows no significant relationship exists between junk food consumption, nutritional status, and physical activity on menarche in adolescents in MTS N 02 Tangerang Regency.